APPLICABILITY OF SCOR-BASED DEA PERFORMANCE MEASUREMENT IN SMALL MED-SIZE ENTERPRISES: A Case Study in Convenience Stores - Bire, Rio Benedicto (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2021)
This paper aims to test the applicability of a SCOR-based DEA benchmarking approach for SMEs in Indonesia, due to the increasing call for suitable supply chain performance measurement in the context of SMEs. An input-oriented DEA assuming both CRS and VRS was employed by deriving a set of metrics from the SCOR attributes. A sample of 16 SME convenience stores was selected for the illustration. Results show that the SCOR-based DEA provided a simple groundwork for supporting SME managerial decision making in terms of administering concise feedbacks and identifying directions to venture on. Moreover, analysis results alluded to a distinct, more comprehensive assessment of performances as opposed to that of traditional measurements that is prominent among SMEs. The distinct, comprehensive insights from the analysis may engage SMEs into taking up the more innovative performance measurement approach. Moreover, better awareness of supply chain metrics is foreseen. The SCOR-based DEA provided a unique approach to meet the conformance of Indonesian SMEs in regard to supply chain performance measurement.